Human platelets contain gelsolin. A regulator of actin filament length. - Lind, S E (1982)
Morphologic and biochemical studies suggest that actin in human platelets polymerizes in response to various stimuli and that shortening of actin filaments can be regulated by calcium. We report that human platelets contain gelsolin, a protein of Mr 91,000 that binds reversibly to actin in the presence of calcium. Platelet gelsolin exhibits immunologic crossreactivity with rabbit macrophage gelsolin and shortens actin filaments as demonstrated by viscosity measurements and gel point determinations. Gelsolin is active in micromolar calcium concentrations and its effects upon actin filaments are reversible. Gelsolin may be a dynamic regulator of actin filament length in the human platelet.